Developing Comprehensive Diabetes Education Materials for Structured Patient Education Programs in Primary Care Setting - Oryzati Hilman Agrimon; Jackie Street (International Journal of Public Health Science (IJPHS), 2016)
Diabetes education is a key factor for a successful diabetes care. Comprehensive diabetes education materials for conducting structured diabetes education programs were rarely found in primary care setting in Indonesia. There was a need for developing new, comprehensive diabetes education materials for low-literate readers. Developing these education materials followed standard steps in developing print materials, and took account tips for writing low literacy materials for poor readers. The new diabetes education materials consisted of ten various leaflets, also printed as14 posters and 14 x-banners. The ten diabetes leaflets were pre-tested to 5 people with type 2 diabetes (T2D). After minor revisions, the leaflets were printed and distributed to 88 people with T2D attending two structured diabetes education programs in Yogyakarta City. These 88 people were requested to evaluate the leaflets using an evaluation form consisting of four items on language usage, font size,  use of pictures, and diabetes information with a 1-10 rating scale; and an open-ended question for improvement. Descriptive statistics were used to analyze the results. Most participants thought that the leaflets were easy to understand and read, interesting, and simple. Majority of participants (79.7%) gave favorable comments without providing suggestions for improvement, such as: “The diabetes leaflets are already good and easy to understand” One third of the participants gave suggestions for improvement. The comprehensive diabetes leaflets developed were well received and highly appreciated by people with T2D attending diabetes education programs.